The Dissolution of Political Parties in Indonesia is Viewed from the Constitutional Aspect - Mursyidi, Mursyidi (Syura: Journal of Law, 2023)
Democracy is a manifestation of the State of Indonesia. This means that Indonesia always triess to guarantee the rights of its citizens to freedom of association and assembly. This is stated in the state constitution, namely the 1945 Constitution concerning guarantees for human rights. This right is the right to associate and assemble which can be dedicated as a forum for establishing a political party. So in matters of the state, it is always related to the problems of political parties. This political party has a role in determining the direction of policies and goals of a country. The development of political parties can also be a development towards the direction of the country, so it is necessary to have restrictions on the establishment of a political party. Like having to have the same ideology with the ideology of the state. Political parties that are proven to have different ideologies from the state will be dissolved and frozen and in this case the dissolution mechanism has been regulated by the state. This change and suspension is a form of restriction given by the state to guarantee national security and also guarantee the rights of Indonesian citizens.